Sto lat metody projektów w Polsce - Pogorzelska, Marzanna (Biuletyn Historii Wychowania, 2017)
A Hundred Years of the Project Method in Poland The text presents the development of the project method in Polish education throughout the last century. The project method was introduced into Poland after regaining independence, and it was implemented during the inter-war period (1918–1939) in some schools, both in urban and rural environments. Nevertheless, the method was at that time treated as a pedagogical novelty and experiment, rather than a natural part of school life. After 1945, education, like other aspects ofsocio-political life, was influenced by the communist propaganda, and the project method, supporting autonomy, democracy and empowerment, was not promoted as a valuable educational approach. After 1989, when progressive trends appeared in Polish schools, the project method gained some popularity but it was not until 2008 when it was granted national and formal recognition. Then, the new core curriculum was developed, and the project method became an obligatory part of school reality. The revival of the project method was connected with the alarming findings concerning social capital in Poland. In this situation, making students cooperate within projects seemed a remedy for the decreasing social capital. As the author points out, formal introduction of the method does not necessarily mean its effective accomplishment, which should be accompanied by spontaneity and authentic engagement. What is more, as the author shows, after decades of the absence of this method in Poland, and the lack of the relevant socio-cultural background, teachers might find it difficult to implement a project so as to contribute to the increase of social capital. All these areas need further investigation. Nevertheless, the author hopes that the text will contribute to better understanding of contemporary challenges and opportunities related to the implementation of the idea of projects in Polish education.